RANCANGAN PRODUK URBAN ACTIVEWEAR UNTUK PEREMPUAN BERTUBUH BESAR - Michaela Rouli Margareta Siahaan; Faradillah Nursasari (Jurusan Seni Rupa ISBI Bandung, 2017)
Activewear is a casual clothing style designed for sport or recreation activities. According to an article released by Global Business Guide Indonesia, activewear is one of the most dynamic categories in selling its products globally. In Indonesia, activewear has recorded a 10% increase since 2013 and is predicted to increase over the next few years. This activewear trend develops in all walks of life in urban society, regardless of their body shapes and social levels. However, major retail brands still focus on selling their products to small and medium size (S and M). Research conducted by Sanjaja and Sudikno (2012) on Prevalence of Overweight and Obesity of Adult Population in Indonesia, concluded that urban people have BMI (Body Mass Index) above average where women aged 20-30 years old have higher excess body weight than men. At this point, the author read the market trends for plus-size women with the size of L-XXL who need a variety of appearances by creating a fashionable urban activewear collection that is inspired by the sub-trend